Family Intervention in the Treatment of Female Juvenile Delinquency : A Qualitative Study in the Collectivist Society of Malaysia - Melati, Sumari; Dini Farhana, Baharudin; Fatahyah, Yahya; Mohd Radhi, Abu Shahim (SAGE Publishing, 2022)
Aims: The current study explores the benefits of a family intervention program on families and their adolescent children who were convicted as juveniles. Adolescents and their families shared their experiences in joining the program, especially the improvement they made while in the program. Demographics: Research participants included eight adolescents, six mothers, and two fathers. Settings: The program took place in Malaysia’s adolescents’ rehabilitation center. Methodology: Data were collected through an in-depth interview with participants. Analysis: Thematic analysis was used to analyze the data. Findings: Findings revealed five main themes: (1) awareness and insight; (2) Understanding risk and protective factors of delinquency; (3) the opportunity to learn roles in the family; (4) Learning to improve communication skills; and (5) Learning to forgive. Implications: The study provides insight into the importance of family involvement in delinquent adolescents’ rehabilitation and the need to consider the family system approach in counseling delinquent adolescents.